(untitled) (Research, Society and Development, 2022)
Introduction: Nipple trauma in infants represents the main causes of early weaning, with a higher prevalence in the immediate puerperium. This problem can be associated with several factors and has as main causes the incorrect positioning and inadequate grip. Objective: To analyze the factors related with nipple trauma in the immediate puerperium, in Amazon. Methodology: this is a primary, clinical, quantitative, cross-sectional, single-centre study, carried out over a period of one month with eight infants hospitalized in the obstetrics department of 2 hospitals, and an evaluation was carried out using a specific instrument containing data related to age, ethnicity, childbirth, breastfeeding, puerperium and pain. Results: The participants had predominantly bilateral clefts, semi-protruded or normal nipples, average appearance of lesions on the second day of life of the newborn, without undergoing treatment for the trauma, with an average VAS of 8. Conclusion: Failure to perform the tongue test stood out, in this study, as the main potential origin of clefts.